Equilibrium modeling in updraft gasifier for refinery sludge gasification using ASPEN PLUS simulator - Ahmed, R. (2013)
The production of refinery sludge has been increasing during tank cleaning, deslugging, and wastewater treatment process. Many efforts have been done to manage the large amount of generated sludge. The gasification of sludge is the most versatile alternative or /and is one potential treatment process for power generation and syngas production. The thermodynamic of gasifier is still not well understood for refinery sludge feedstock. As far as optimising the operational conditions of gasification process is concerned, a successful simulated work is introduced by making use of ASPEN PLUS software simulator. This software was tailored and developed to describe an equilibrium model in updraft gasifier of dry refinery sludge (DRS). The textural characteristic properties of refinery sludge are shown in this paper (ultimate and proximate analysis). In the present study four parameters (i.e. oxidation zone temperature, operating pressure, air flow rate (l/min) and equivalent ratio) were analyzed. In the present work, details of the equilibrium model are presented. This model shows a better agreement with literature model for biomass gasification. From our model results, the mass fractions yield of the desired products (CO and H2) increases as the oxidation zone temperature increases while their yield decreases after 3 bar. The desired products are found to decrease as the air flow increases while CO2 mass fraction favors high air/fuel ratio. The model results are validated by comparison with experimental data issued from the literature. Â© (2013) Trans Tech Publications, Switzerland.